Bilateral Hip Joint Hylan G-F 20 Granulomatous Synovitis due to Viscosupplementation Injections - Patrick Weinrauch; Robert Trigger; George Tsikleas (Case Reports in Orthopedics)
We present the diagnosis of bilateral granulomatous inflammation of the hip joints associated with Hylan G-F 20 viscosupplementation injections. Clinicians recommending therapeutic Hylan injections for the management of hip arthritis should maintain clinical awareness regarding this potential complication.